2019
DOI: 10.1007/s10811-019-01966-8
|View full text |Cite
|
Sign up to set email alerts
|

24-Epibrassinolide modulates primary metabolites, antioxidants, and phytochelatins in Acutodesmus obliquus exposed to lead stress

Abstract: Aquatic organisms are exposed to many stressors, e.g., heavy metals. Brassinosteroids, a plant hormone group, can effectively stimulate plants to defend against the negative impact of a heavy metal. The present study was conducted with an aim to find out the influence of 24-epibrassinolide (EBL) on Acutodesmus obliquus treated with 0.01 and 500 μM of lead (Pb) ions during 7 days of cultivation. Pb has a toxic effect on algal cultures because it limits both the growth and development and induces oxidative stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 82 publications
(109 reference statements)
2
9
0
Order By: Relevance
“…The influence of heavy metals on chlorophylls and carotenoids with separated xanthophyll content was studied in algae and agricultural uses. Similar to our results, Pb caused a decrease in pigment amount in Acutodesmus obliquus [ 50 , 51 ]. In the current work, the reduced level of pigments was observed under the influence of Cd.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The influence of heavy metals on chlorophylls and carotenoids with separated xanthophyll content was studied in algae and agricultural uses. Similar to our results, Pb caused a decrease in pigment amount in Acutodesmus obliquus [ 50 , 51 ]. In the current work, the reduced level of pigments was observed under the influence of Cd.…”
Section: Discussionsupporting
confidence: 92%
“…The retention times of GSH and PCs were established using their standards. The wavelengths of excitation and emission were 380 and 470 nm, respectively [ 51 , 81 ].…”
Section: Methodsmentioning
confidence: 99%
“…The reduction in plant growth by heavy metal toxicity is related to the number of intercellular metal ions bound to the surface of the cell [86,87]. Our results showed that EBL could increase the plant biomass and plant growth under heavy metal toxicity, which could be related to the role of EBL in the reduction in intercellular metal ions, a phenomenon that has been confirmed in a study on A. obliquus [63]. However, the role of EBL in plant growth regulation during the stimulation of plant defense mechanisms can also be considered.…”
Section: Discussionsupporting
confidence: 80%
“…Conversely, EBL has the ability to positively alter the membrane structure and membrane stability in plants exposed to stresses, such as heavy metals, which leads to a reduction in membrane lipid peroxidation [62]. In one study, the level of EBL was observed to diminish the concentrations of H 2 O 2 and MDA (20-60% reductions) in plants under Pb stress [63]. In another study, EBL diminished the oxidative toxicity in cowpea under Cd by reducing lipid peroxidation, MDA content, and electrolytes [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…The chelation of the metal ions by phytochelatins is one of the mechanisms for heavy metal detoxification in plants (Talarek‐karwel et al . 2020). Phytochelatins are cysteine‐rich polypeptides derived from glutathione (Batista et al .…”
Section: Discussionmentioning
confidence: 99%